Mental Health Nursing Care for Mrs. R with the Main Issue of Risk of Violent Behavior Due to Paranoid Schizophrenia in the Brotojoyo Ward, Dr. Amino Gondohutomo Psychiatric Hospital - Vera Shinta Dewi; Titi Sri Suyanti; Slamet Wijaya Biantoro (Java Nursing Journal, 2024)
Background: Paranoid schizophrenia is a mental disorder characterized by severe psychopathological symptoms, including delusions and hallucinations, which often lead to a risk of violent behavior. Purpose: This case study aims to provide nursing care for patients with paranoid schizophrenia at RSJD dr. Amino Gondohutomo, Central Java. The case discussed involves Mrs. R, who experiences a risk of violent behavior as a consequence of paranoid schizophrenia. Methods: The method used in this discussion is a case study with a mental health nursing care approach, including assessment, nursing diagnosis, intervention, implementation, and evaluation. Results: The results of the nursing care show that appropriate interventions, such as physical and verbal anger control exercises, as well as spiritual approaches, can reduce the intensity of violent behavior in the patient. Family support and patient compliance in undergoing pharmacological therapy also play a significant role in the recovery process. Conclusion: In conclusion, comprehensive and collaborative nursing care can improve the patient's psychological condition and reduce the risk of violent behavior.